Induction of Vasoactive Substances Differs in LPS-Induced and TF-Induced DIC Models in Rats - Asakura, Hidesaku; Okudaira, Mariko; Yoshida, Tomotaka; Ontachi, Yasuo; Yamazaki, Masahide; Morishita, Eriko; Miyamoto, Ken-ichi; Nakao, Shinji (Thrombosis and Haemostasis, 2002)
We have investigated the role of two vasoactive substances, nitric oxide (NO) and endothelin (ET), in the pathophysiology of disseminated intravascular coagulation (DIC), using two types of DIC models. Experimental DIC was induced by sustained infusion of 0.1, 1, 10, or 50 mg/kg lipopolysaccharide (LPS), or 3.75 U/kg thromboplastin (TF), for 4 h via the rat tail vein. Plasma levels of both NOX (metabolites of NO) and ET were significantly increased following infusion of 0.1 mg/kg or greater of LPS in the LPS-induced DIC rat model. In contrast, although a marked increase in the plasma levels of NOX was observed, only a slight increase in plasma ET levels was seen in the TF-induced DIC rat model. No significant differences in the plasma levels of platelets or thrombin-ATIII complex were observed among the TF-induced and LPS (50 mg/dl)-induced DIC models. However, plasma NOX levels rose significantly higher in the TF-induced model, relative to the LPS-induced model (p <0.01). Conversely, plasma ET levels were significantly greater after LPS-induction, compared to TF-induction, of DIC (p <0.01). Vasoconstriction, as well as depressed fibrinolytic activity, may be additional factors leading to severe organ dysfunction in the LPS-induced DIC rat model. Moreover, vasodilatation, as well as enhanced fibrinolytic activity, may help to prevent rats from severe organ dysfunction in the TF-induced DIC model. Our results suggest that modulator of vasoactive substances should be examined in the treatment of DIC.
Keywords: Disseminated intravascular coagulation; tissue factor; lipopolysaccharide; endothelin; nitric oxide